Corporate social responsibility and assurance disclosure practice: an investigation of the top 100 companies in Bangladesh. (2018) - Sobhan, Nawreen; Hassan, Abeer; Fletcher, Mary
This study investigates the link between assurances practices of corporate social responsibility (CSR) reports using the top 100 Bangladeshi companies in the year 2015 based on the global reporting initiatives (GRIs). The main objective is to find out to what extent companies in Bangladesh assure their CSR activities. To achieve the research objectives, three research questions are developed to examine the interrelationships between assurance and CSR disclosure, industry sector, and reporting format. We find that, in general, Bangladeshi companies tend to assure their disclosure in the areas of economic performance, labour and society. We find that non-carbon Bangladeshi companies tend to get their CSR disclosure assured. We also find that Bangladeshi companies which adopt assurance tend to disclose more CSR activities on their annual report. Our results, in general, support proactive legitimacy theory as they provide evidence that Bangladeshi companies proactively disclose CSR information in certain areas and seek assurance to enhance stakeholders' confidence and credibility of social and environmental reporting.